Compared analysis of the economic and environmental benefits by using an energy management system in different European countries. (September 2017) - Azuma, Hiroshi; Magnani, Sandro
Abstract: The European Union has approved a new energy strategy for 2030, the target being to save the 27% of primary energy compared with the business-as-usual scenario and to reduce the CO2 emission of 40%. Each member state shall establish an indicator showing the energy efficiency contribution towards the Member State's 2030 target. Under such challenging target, the use of optimized energy management system has the potential to greatly contribute to the reduction of both the primary energy and the CO2 emission. Of course, the economic benefit for installing these systems is also an important issue from owner's point of view, and it has a big influence on the technical solution choice. The energy management systems are capable to optimize the schedule of boilers, electric chillers, and other kind of generators. In this latter case, the use of cogeneration systems is often applied, in order to increase the overall efficiency of the plant, often in combination with absorption chillers to make effective use of the heat also with large cooling loads and small heating duties. The fuel sources of all these pieces of equipment are represented by natural gas and electricity, so the result of optimized operations is greatly modified depending on the situation of gas and electricity prices, which are strictly dependent on the country which the analysis is referred to. The purpose of this study is to clarify the influence of the electricity price and the natural gas price of each country on the optimum operation of an energy management system, considering the acquired energy demand pattern and the configuration of a multi-generation production plant consisting in a small Italian factory. The energy price scenarios which will be analyzed are related to 7 countries with large GDP in the EU region, on which optimization algorithm will be applied. The results will be focused on the comparison of the economic benefit, primary energy saving and reduction of CO2 emissions for each country, applying different target function of the optimizer (minimum running costs, primary energy consumption, or GHGs emissions), in order to highlight the most relevant parameters determining the benefit of the energy management system.